Gold Nanoparticles in Porous Silicon Nanotubes for Glucose Detection - Roberto Gonzalez-Rodriguez; Evan Hathaway; Jeffery L. Coffer; Roxana M. del Castillo; Yuankun Lin; Jingbiao Cui (Chemosensors, 2024)
Silicon nanotubes (Si NTs) have a unique structure among the silicon nanostructure family, which is useful for diverse applications ranging from therapeutics to lithium storage/recycling. Their well-defined structure and high surface area make them ideal for sensing applications. In this work, we demonstrate the formation of Au nanoparticles (NPs) functionalized with 4-Mercaptophenylboronic acid (MPBA) on porous Si NTs (pSi NTs) fabricated using ZnO nanowires as a template. The system was characterized, and the proposed structure was confirmed using scanning electron microscopy (SEM), transmission electron microscopy (TEM), and X-ray photoelectron spectroscopy (XPS). Varying glucose concentrations in phosphate-buffered saline (PBS) (0.5–80 mM) were introduced to the Si NT nanocomposite system. The glucose is detectable at low concentrations utilizing surface-enhanced Raman spectroscopy (SERS), which shows a concentration-dependent peak shift in the benzene ring breathing mode (~1071 cm−1) of MPBA. Complementing these measurements are simulations of the Raman hot spots associated with plasmonic enhancement of the Au NPs using COMSOL. This biocompatible system is envisioned to have applications in nanomedicine and microfluidic devices for real-time, non-invasive glucose sensing.